2019
DOI: 10.15252/embr.201948216
|View full text |Cite
|
Sign up to set email alerts
|

Afadin is a scaffold protein repressing insulin action via HDAC 6 in adipose tissue

Abstract: Insulin orchestrates metabolic homeostasis through a complex signaling network for which the precise mechanisms controlling its fine‐tuning are not completely understood. Here, we report that Afadin, a scaffold protein, is phosphorylated on S1795 (S1718 in humans) in response to insulin in adipocytes, and this phosphorylation is impaired with obesity and insulin resistance. In turn, loss of Afadin enhances the response to insulin in adipose tissues via upregulation of the insulin receptor protein levels. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 49 publications
(59 reference statements)
5
32
0
Order By: Relevance
“…2 f). In accordance with our previous study 13 , these data show that adipogenesis was not affected by repression of Afadin. Interestingly, there was a twofold increased expression of Mllt4 –the gene encoding Afadin- upon differentiation (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…2 f). In accordance with our previous study 13 , these data show that adipogenesis was not affected by repression of Afadin. Interestingly, there was a twofold increased expression of Mllt4 –the gene encoding Afadin- upon differentiation (Fig.…”
Section: Resultssupporting
confidence: 94%
“…1 a,c), presumably driven by cold-mediated lipolysis in white adipose tissue stimulating insulin secretion 10 . We have recently shown that Afadin is phosphorylated at S1795 in response to insulin via Akt 13 , and found that Afadin S1795 phosphorylation was also increased upon 3 h of cold exposure (Fig. 1 a,d).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Ten 9-11-week-old male C57BL/6 J mice were fasted for 4 h and anaesthetized, followed by retro-orbital injection of 1 unit insulin/saline for 5 min (5 mice per group). For the fasting/refeeding challenge, 9-week old male mice were fasted overnight, refed for either 2 or 6 h (6 mice per group), and euthanized [27]. For the high-fat diet challenge, 6-week old male mice were fed with either control diet (D12450B, Research Diets, Inc., USA) or high-fat diet (D12492, Research Diets, Inc., USA) for 8 weeks.…”
Section: Animal Housing and Dietmentioning
confidence: 99%
“…HDACs belong to a family of enzymes that deacetylate acetylated proteins, consequently influencing cellular physiological process 11 . Emerging evidence suggests that HDACs involves in the development of diabetes 12 and DN 11 . Selective inhibition of HDACs, such as HDAC2, HDAC4, HDAC7 or HDAC9, improves apoptosis, autophagy, inflammation, excessive accumulation of ECM and renal fibrosis in DN 7,11,13 .…”
Section: Introductionmentioning
confidence: 99%